Pengaruh Budaya Organisasi Dan Teknologi Informasi Terhadap Kinerja Pegawai Dengan Motivasi Sebagai Variabel Intervening : Studi Kasus: Pegawai Fakultas Kedokteran Dan Kesehatan Universitas Muhammadiyah Jakarta - Tri Wahyudi; Derriawan; Fahruddin Salim (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The purpose of this study was to determine whether there is a significant influence between Organizational Culture and Information Technology on Employee Performance with Motivation as an Intervening Variable for Employees at the Faculty of Medicine and Health, University of Muhammadiyah Jakarta. The research used in this research is quantitative research. The quantitative research method is a type of research whose specifications are systematic, planned and structured from the start to the creation of the research design. Data management in this study will use smart PLS 3.2.6 Software Structural Equation Modeling (SEM) is a method used to cover the weaknesses found in the regression method. While the sample technique used is probability sampling, while the sampling method used is simple random sampling using a total sample of 60 people.